2009
DOI: 10.1097/shk.0b013e318193c35d
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Bolus Injection, but Not Continuous Infusion of Sodium Selenite Improves Outcome in Peritonitis

Abstract: Administration of sodium selenite in septic shock has been associated with apparently conflicting results that may be related to different dosing schedules. Bolus administration, leading to a transient pro-oxidative effect, could limit the inflammatory reaction and improve outcomes. We studied 21 anesthetized, mechanically ventilated, invasively monitored, and fluid-resuscitated sheep. Nine hours after inducing peritonitis by injection of autologous feces, the animals were randomized into three groups: (i) bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 33 publications
3
53
1
Order By: Relevance
“…The effect was evident only in males, suggesting a sex-specific relationship between Se status and sepsis. An animal model of sepsis utilizing sheep demonstrated that a large-bolus injection of Se (2 mg Se as sodium selenite) had more beneficial effects than continuous administration of Se (4.0 lg/kg per h) (263), although the conclusions of this study require follow-up investigation to determine if these results are duplicated in humans. In humans, treatment of critically septic patients with Se supplementation seems to improve clinical outcome in terms of infections and organ failure (8,205), but larger intervention studies are required before conclusive results can be obtained.…”
Section: B Critical Illness Stress-induced Immune Suppressionmentioning
confidence: 91%
“…The effect was evident only in males, suggesting a sex-specific relationship between Se status and sepsis. An animal model of sepsis utilizing sheep demonstrated that a large-bolus injection of Se (2 mg Se as sodium selenite) had more beneficial effects than continuous administration of Se (4.0 lg/kg per h) (263), although the conclusions of this study require follow-up investigation to determine if these results are duplicated in humans. In humans, treatment of critically septic patients with Se supplementation seems to improve clinical outcome in terms of infections and organ failure (8,205), but larger intervention studies are required before conclusive results can be obtained.…”
Section: B Critical Illness Stress-induced Immune Suppressionmentioning
confidence: 91%
“…We observed the lowest Sel-P plasma concentrations in nonsurviving septic-shock patients, which supports our hypothesis of a protective effect of Sel-P on the endothelium in sepsis. The results of our recent study using an experimental model of peritonitis in sheep showed that the decrease in plasma Se concentration seems to appear very rapidly in sepsis and to precede the onset of septic shock [37] . Therefore, in persistent generalized oxidative stress, as observed in the microcirculation during septic shock, a marked decrease in plasma Sel-P concentration may lead to enhanced endothelial dysfunction, microvascular injury and multiple-organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in plasma Se may be a strong mortality marker in septic surgical patients admitted to an intensive care unit (ICU) [36] . Moreover, it has been observed in an ovine model of peritonitis that plasma Se concentration decreased within 9 h after the onset of peritonitis [37] , suggesting that the decrease in plasma Se concentration could appear early in human sepsis. However, the reason for this marked decrease in plasma Se remains unclear and may be related to changes in plasma concentrations of either Sel-P, GPx or albumin that account for 53, 39 and 9%, respectively, of the total plasma Se in healthy individuals [18,38] .…”
mentioning
confidence: 99%
“…18 We may have prescribed an insufficient dose of selenium or used an ineffective dosing schedule, since a higher-thannormal level of selenium in the blood may be associated with the best outcome 19 and an initial bolus of selenium might have been more effective than the continuous administration we used. 20 The strengths of this study include the randomized and blinded design, rigorous determination and adjudication of infection, and intention-to-treat analysis, all of which augment the internal validity of the trial. The high rate of adherence to trial interventions, large number of patients, and enrollment in ICUs in North America and Europe bolster the external validity.…”
Section: Discussionmentioning
confidence: 99%